THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE AND DEBT POLICY ON FIMR VALUE WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE IN BASIC INDUSTRY AND CHEMICAL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Herdini Br Sitepu; Rina Br. Bukit; Sirojuzilam Hasyim (CV. Radja Publika, 2025)
This study examines the effect of Environmental, Social, and Governance (ESG) disclosure and debt policy on firm value, with institutional ownership as a moderating variable. The research focuses on basic industry and chemical sector companies listed on the Indonesia Stock Exchange (IDX) during 2021-2024. Using a quantitative approach with secondary data from annual reports, sustainability reports, and financial statements, this study employs purposive sampling resulting in 30 companies with 120 observations. Data analysis utilizes panel data regression. The results indicate that ESG disclosure has a positive and significant effect on firm value, while debt policy has a negative effect on firm value. However, institutional ownership cannot strengthen the relationship between ESG and firm value. Conversely, institutional ownership actually weakens the effect of debt policy on firm value. This research provides contributions for company management, investors, and regulators to pay more attention to ESG disclosure as a strategy to enhance firm value, while carefully considering capital structure in the context of institutional ownership.